Introduction to Bioinformatics in Microbiology - Henrik Christensen (Springer, 2018)
This textbook introduces to the basic concepts of bioinformatics and enhances students' skills in using software and tools relevant for investigations in microbiology. The most relevant methods to analyze data are shown and readers are introduced on how to draw valid conclusions based on the results obtained. Software and servers which are free to use on the internet are presented and more advanced stand-alone programs are suggested as a second option. Exercises and training quizzes are provided at the end of each chapter to facilitate learning. The book targets Ph. D. students and advanced undergraduates in microbiology, biotechnology, and (veterinary) medicine with little to basic knowledge in bioinformatics.